Особенности ангиоархитектоники сердца собаки (Canis domesticus L.) - Мельман, Е.П.; Шевчук, М.Г. (Вестник зоологии, 1972)
Peculiarities of architectonic of dog heart coronary artery were investigated up to the capillaries by the methods of angio- and stereoroentgenography and macro-microscopy on the whole preparations and slices. The ways of microcirculation inside the wall of each of the four heart chambers were studied in detail: It was established that distribution of heart coronary arteries and their anastomoses in dogs differ from this distribution in man (in dogs, as a rule, the form artery disribution is left-coronary; in interventricular septum of dog the branches of the left coronary artery anastomose between themselves and in man — right and left etc.). All this should be taken into account when carrying the experiments with dogs and transferring their results to clinical practice.